Consequences of perinatal bisphenol A exposure in a mouse model of multiple sclerosis. (February 2014) - Brinkmeyer-Langford, Candice; Rodrigues, Aline; Kochan, Kelli J.; Haney, Rachel; Rassu, Fenan; Steelman, Andrew J.; Young, Colin; Riggs, Penny; Storts, Ralph; Meagher, Mary W.; Welsh, C. Jane
Abstract Multiple sclerosis (MS) is a complex disease influenced by genetic and environmental contributing factors. Endocrine disrupting compounds (EDCs) such as bisphenol A (BPA) affect gene expression and hormone-regulated systems throughout the body. We investigated the effects of BPA on Theiler's-virus induced demyelination (TVID), a mouse model of MS. Perinatal BPA exposure, combined with viral infection, resulted in a decreased level of viral antibodies, accelerated the onset of TVID symptoms, increased inflammation in both the spinal cord and digestive tract, and amplified immune-related gene expression changes induced by viral infection. These results demonstrate the effect of BPA on the trajectory of TVID, and illustrate how multiple factors collectively influence autoimmune disease.